Calories and Culture: Food, Drink, and the British Army in Early Nineteenth Century Upper Canada - Breadman, Jake (Ontario History, 2023)
This article analyzes what British soldiers in early-nineteenth century Upper Canada consumed in both peace and wartime, and how food and drink impacted human social relations between soldiers, officers, and Indigenous people. Consumption is about getting enough energy to survive, but it can also bind or break social relations. Here, both calories and culture, and the intrinsic connection between them, are analyzed. The first section looks at the calories which soldiers procured from food beyond their daily rations: fishing, agriculture and, sometimes, hunting and purchase. Out of these, fishing and hunting particularly divided enlisted men and officers. The availability of consumables, though, depended on class and environmental knowledge. Then the difficulties of hunting and fishing in wartime are outlined. Section two turns to culture: food and drink, and the rituals and settings surrounding consumption, positively and negatively impacted human social relations within the British army and with Indigenous people.